2008
DOI: 10.1016/j.cub.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Gr64f Is Required in Combination with Other Gustatory Receptors for Sugar Detection in Drosophila

Abstract: Summary The mechanisms by which the fruitfly, Drosophila melanogaster, detect sweet compounds are poorly understood; however, a subset of the family of 68 gustatory receptors (Grs) has emerged as the key receptors. These seven transmembrane receptors include Gr5a and at least one member of the six genes in the Gr64 cluster (Gr64a), which are expressed in sugar-responsive neurons. Disruption of Gr5a prevents the detection of trehalose [1–3], while mutation of Gr64a impairs the responses to sucrose, maltose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
234
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(239 citation statements)
references
References 22 publications
5
234
0
Order By: Relevance
“…A similar result was also reported in studies of other Drosophila GRs to detect caffeine, theophylline, sucrose, d-glucose as well as trehalose (Dahanukar et al 2001;Dahanukar et al 2007;Jiao et al 2008;Jones et al 2007;Moon et al 2006). In the mosquito A. aegypti, RNA interference (RNAi)-mediated gene knockdown of either AaegGR21a or AaegGR63a resulted in a loss of CO2 sensitivity, suggesting that these two proteins function as a heterodimer just as DmelGR21a and DmelGR63a do in Drosophila.…”
Section: Discussionsupporting
confidence: 81%
“…A similar result was also reported in studies of other Drosophila GRs to detect caffeine, theophylline, sucrose, d-glucose as well as trehalose (Dahanukar et al 2001;Dahanukar et al 2007;Jiao et al 2008;Jones et al 2007;Moon et al 2006). In the mosquito A. aegypti, RNA interference (RNAi)-mediated gene knockdown of either AaegGR21a or AaegGR63a resulted in a loss of CO2 sensitivity, suggesting that these two proteins function as a heterodimer just as DmelGR21a and DmelGR63a do in Drosophila.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have focused on the expression and function of these Grs in taste organs that have access to external sensory cues including the labellum, the pharyngeal organs, and the tarsi (Isono and Morita, 2010;Thorne et al, 2004;Wang et al, 2004;Weiss et al, 2011). Gr5a, Gr64a, and Gr64f, which are members of a Gr subfamily of eight Grs, were found to act as sugar sensors through genetic approaches Jiao et al, 2008;Slone et al, 2007), and Gr33a, Gr66a, and Gr93a were found to be required for responses to caffeine and certain other bitter compounds Moon et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, our results indicate that synephrine specifically induces a change of Ca concentration via signal transduction mediated by the expression of PxutGr1 in Sf9 cells. Receptors for sweet and bitter tastes in Drosophila are known to form heterodimers with co-receptors to recognize the tastant 18,19,38,39 . At the moment, we do not exclude a possibility that PxutGr1 requires a similar coreceptor that may enhance the specific response of the receptor to synephrine in our calcium imaging assay.…”
mentioning
confidence: 99%